Factors Related To The Implementation Of Communication With The Sisbar Method ( Salam Introduction Situation Background Assessment Recommendation ) At Medical-Surgical Wards In Santosa Hospital Bandung Central - Dedi Supriadi; Asep Badrujamaludin (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2022)
This study focus on is there any connection between factors ( age , gender , length of work and origin room ) with implementation communication with the SISBAR (Salam Introduction Situation Background Assessment Recommendation) method. This Study use cross sectional design. Sample of this study is the total sample nurse in charge who implementation SISBAR communication (West Safir , East Safir , West Berlian and Mutiara wards) in Santosa Hospital Bandung Central that fulfills inclusion criteria sample totaling 44 nurses.The method used total sampling technique that whole population made sample on this research. Analysis bivariate used for seeing connection between 2 variables (independent and dependent). Analysis is conducted for see meaningful relationship by statistics, use statistical test Chi Square with level 95% confidence (?=0.05).Analysis test results statistics using the Chi Square test obtained p-Value: 0.048 (variable age ), 0.004 (variable education ) and 0.011 (variable length of work ), while the other two factors are not connection with p value for each of these factors is 1,000 (variable type gender ) and 0.791 ( original variable room ). It means there is connection between the variables of age , education and length of work, whereas variable gender and origin room is no relationship with implementation communication effective with SISBAR method between nurses and doctors.SISBAR communication can be developed and enhanced for effective communication between nurses and doctors in other hospitals in Indonesia with pay attention to the factors that influence it.